Spanish honour - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
Recent reports in Spore of CTA activities have covered seminars held in Spain and other Spanish-speaking countries. They include the Cordoba water seminar, Santo Domingo organic banana meeting (see In Brief), and two seminars in Madrid on marketing...